Exploring the Benefits of Extensive Viewing for EFL Learners - Rosyida, Hawla; Entusiastik, Entusiastik; Wulandari, Sri (Universitas Islam Lamongan, 2025)
English language learning can be enhanced through engaging methods such as extensive viewing. This study aims to explore the benefits of extensive viewing and find out the perceptions of EFL students regarding its use. Extensive viewing is a concept for acquiring a second language (L2), where students watch TV, film, or video and use media according to their interests. This research employs qualitative methods, utilizing a case study approach, then exploring and describing the benefits of extensive viewing in acquiring knowledge or skills in English or a second language. The instruments of this research are questionnaires, interviews, and diary studies administered to 128 FKIP Uniska students who are English as a Foreign Language Learners. This research adopts constructivist theory, where students actively construct knowledge through self-directed, interest-based activities rather than passively receiving information. The data analysis used in this research is thematic analysis. The results of this study highlight both the benefits and challenges of implementing extensive viewing, as well as learners’ perceptions of its effectiveness.